Transformasi Pendekatan Blok Saraf Sensoris sebagai Strategi Prosedur Bebas Nyeri - Reno Yonora (MEDICINUS, 2026)
Pain during medical procedures remains a major challenge in clinical practice, particularly in minor surgery and simple invasive procedures. Conventional local anesthetic infiltration techniques frequently cause additional pain, tissue distortion, and suboptimal anesthetic distribution, highlighting the need of a simpler, more effective, patient-centered approach. The sensory nerve block targets peripheral sensory nerve branches as distal extensions of the central nervous system. Through strategic selection of insertion points, extensive anesthetic coverage can be achieved with only one or two injection points without the need for extensive tissue infiltration. This article discusses the concept, mechanism of action, and clinical applications of sensoric nerve block as a strategy toward minimally painful medical procedures. This technique offers rapid onset, minimal anesthetic requirements, improved patient comfort, as well as greater procedural efficiency. Given these advantages, this approach has the potential to become a new paradigm in modern medical practice, particularly in various minor surgical procedures.